Career Development of Generation Z through Technology and Media: Implementation in Vocational High Schools - Nina Permata Sari; Eklys Cheseda Makaria; Muhammad Andri Setiawan; Nurul Andri Azkiya; Muhammad Umar Marani (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
This article examined the implementation of a workshop as a preparatory strategy for Generation Z students at SMK Negeri 3 Banjarmasin to face increasingly complex career challenges. The workshop aimed to deepen students’ comprehension of utilizing technology and media in career services. The research involved 33 tenth-grade students who were evaluated through pre-tests and post-tests regarding their understanding before and after the workshop on September 24-30, 2023. The pre-test results showed positive evaluations, with the majority of participants considering the workshop to have provided accurate career information (90.9%) and to be relevant to the latest developments in the job market (90.9%). After the workshop, there was a positive improvement in participant assessments. Understanding of technological developments increased to 87.9%, while the ability to utilize technology reached 90.9%. The workshop was considered effective in developing career skills (81.8%) and guiding students to optimize their talents for the job market (84.9%). The workshop followed the Asset-Based Community Development (ABCD) approach, recognizing students as unique individuals with potential that can be developed. The design stage involved identifying student assets, participatory planning, and focusing on the use of technology as a key aspect of career development. The workshop participants were 33 10th-grade students, selected based on the specific needs of the first batch. The ABCD approach considered student diversity, encouraging active participation in every workshop session. Data collection applied the ABCD approach with participatory methods, while instrument development involved local assets and relevant technology. Data analysis included quantitative statistical analysis and comparison of pre-test and post-test questionnaire results to measure changes in student understanding. Overall, the workshop was effective in improving students’ understanding of career trends, skill development, and technology utilization. These results affirmed the role of the workshop as a strategic tool in equipping Generation Z to face the dynamics of the competitive job market.